Knee-joint exoskeleton control system design using adaptive barrier function controller - Amer B. Rakan; Mohammed Rashid Subhi; Ali H. Mhmood (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Exoskeletons and wearable robots are mechatronic devices that are worn by an operator and fit closely to the body to improve daily activities. The adaptive sliding mode control (ASMC) based on the barrier function is proposed in this study to regulate the movement of the knee joint exoskeleton with friction. This controller is implemented without the requirement to know the system model uncertainty and disturbance bounded and does not require the use of the low pass for chattering elimination with keeping the controller’s performance. The suggested barrier method can be guaranteed the output variable’s convergence and keep it in a preset neighborhood of zero regardless of the disturbance’s upper bound, without overestimating the control gain. The simulation results show that the proposed performs well, the system angle following the target angular position with a modest pre-adjusted steady-state error. Furthermore, when compared to a typically strong and stable ASMC developed with the identical actuator; the obtained results reveal superior features. Concluded from the above this control method indicates the robustness of the proposed adaptive controller with barrier function against uncertainties and disturbances elimination.